A bistatic laser monitor - Trigub M. V. Maksim Viktorovich; Torgaev S. N. Stanislav Nikolaevich; Evtushenko G. S. Gennady Sergeevich; Troitsky V. O. Vladimir Olegovich; Shiyanov D. V. Dmitry Valeryevich (2016, 2016)
Title screen